Discovering an unknown territory using atom probe tomography: Elemental exchange at the bioceramic scaffold/bone tissue interface. (May 2023) - Holmes, Natalie P.; Roohani, Iman; Entezari, Ali; Guagliardo, Paul; Mirkhalaf, Mohammad; Lu, Zufu; Chen, Yi-Sheng; Yang, Limei; Dunstan, Colin R.; Zreiqat, Hala; Cairney, Julie M.
Abstract: Here we report the first atom probe study to reveal the atomic-scale composition of in vivo bone formed in a bioceramic scaffold (strontium-hardystonite-gahnite) after 12-month implantation in a large bone defect in sheep tibia. The composition of the newly formed bone tissue differs to that of mature cortical bone tissue, and elements from the degrading bioceramic implant, particularly aluminium (Al), are present in both the newly formed bone and in the original mature cortical bone tissue at the perimeter of the bioceramic implant. Atom probe tomography confirmed that the trace elements are released from the bioceramic and are actively transported into the newly formed bone. NanoSIMS mapping, as a complementary technique, confirmed the distribution of the released ions from the bioceramic into the newly formed bone tissue within the scaffold. This study demonstrated the combined benefits of atom probe and nanoSIMS in assessing nanoscopic chemical composition changes at precise locations within the tissue/biomaterial interface. Such information can assist in understanding the interaction of scaffolds with surrounding tissue, hence permitting further iterative improvements to the design and performance of biomedical implants, and ultimately reducing the risk of complications or failure while increasing the rate of tissue formation. Statement of significance: The repair of critical-sized load-bearing bone defects is a challenge, and precisely engineered bioceramic scaffold implants is an emerging potential treatment strategy. However, we still do not understand the effect of the bioceramic scaffold implants on the composition of newly formed bone in vivo and surrounding existing mature bone. This article reports an innovative route to solve this problem, the combined power of atom probe tomography and nanoSIMS is used to spatially define elemental distributions across bioceramic implant sites. We determine the nanoscopic chemical composition changes at the Sr-HT Gahnite bioceramic/bone tissue interface, and importantly, provide the first report of in vivo bone tissue chemical composition formed in a bioceramic scaffold. Graphical abstract: Image, graphical abstract